Merawat Pengalaman Mistik dalam Liturgi: Memanfaatkan Olah Batin Lepas Bebas dalam Penyusunan Liturgi - Wisnu Tri Handayani (KENOSIS: Jurnal Kajian Teologi, 2022)
Worship is the encounter between God and the people. Through worship, God speaked to us and vice versa. This intimacy with God or mystical experience is the essence of worship. People were expecting to experience this intimacy trough all the liturgical elements prepared by the liturgy composer. Worship become mechanistic ritualism when it designed without realizing, anticipating, and preparing for mystical experiences. Worship is no longer a medium for people to experience intimacy with God. This article examines about mystical experiences in designing liturgy trough detachment of meister Eckhart. Qualitative interview of seven respondents and study abaut detachment of Eckhart were the methods used in this article. The process of designing liturgy that involves bible study and other materials, also inspiration and guidance from the holy spirit were mystical experiences. Through detachment, these experiences were prepared, anticipated, and improved. This research helps the liturgy composer to design liturgy that emerge from mystical experience. Furthermore, they can prepare, anticipate, and improve mystical experience from the liturgy that they designed. Therefore they can nurture the essence of liturgy.   AbstrakIbadah adalah perjumpaan manusia dengan Allah. Melalui ibadah, umat disapa Allah dan sebaliknya. Pengalaman kedekatan dengan Allah atau mistik inilah esensi ibadah Unsur-unsur ibadah dipersiapkan dan ditata dengan harapan orang yang beribadah memperoleh pengalaman tersebut. Menyusun liturgi tanpa menyadari, mengantisipasi, dan mempersiapkan pengalaman mistik membuat ibadah jatuh pada ritualisme mekanistik. Ibadah tidak lagi menjadi medium bagi umat mengalami kedekatan dengan Allah. Tulisan ini mempercakapkan bagaimana merawat pengalaman mistik dalam penyusunan liturgi melalui olah batin lepas bebas. Metode yang digunakan adalah wawancara kualitatif terhadap tujuh responden dan kajian pustaka tentang pengalaman mistik melalui olah batin lepas bebas dari Meister Eckhart. Aktivitas menyusun liturgi yang melibatkan studi Kitab Suci dan bahan penunjang lainnya serta tuntunan Roh Kudus yang menginspirasi merupakan pengalaman mistik. Pengalaman mistik dapat diantisipasi melalui olah batin lepas bebas. Pengetahuan ini menolong penyusun liturgi menjalankan perannya yang bersumber dari pengalaman mistik. Selain itu, mereka dapat mempersiapkan dan mengantisipasi pengalaman mistik dalam ibadah. Dengan begitu pengalaman mistik dalam ibadah terpelihara.